Impact of the Sovereign Debt Crisis on the Determinants of the Capital Structure in Real Estate and Construction Related Firms - Evidence from Portugal - Luís Filipe Ribeiro Cruz (2018)
Portugal was one of the most affected countries by the sovereign debt crisis, whose impact was felt mostly in the peripheral European countries, being one of the reasons for the development of this topic. We have focused on only one industry, being the real estate and construction related firms, because there are few studies that make an exhaustive study on industries. Additionally, this industry in particular, is very pro-cyclical, in the sense that depends a lot on the existence of good economic conditions to gather construction contracts as well as public investment. The purpose of this dissertation is to understand if the sovereign debt crisis had an impact over the capital structure of the companies and on the firm-specific variables. There are some theories that try to explain how companies decide about their capital structure that alongside with the support of empirical studies were used in the formulation of several hypotheses.An unbalanced panel of 404 firms, whose information was gathered from the database SABI Bureau Van Dijk, was used in the econometric estimations. We have estimated two main models for four different dependent variables, namely debt ratios, because we wanted to assess how different maturities of debt were affected by the crisis. In the end, we provide evidence of a reduction in the debt ratios during the period of crisis, which may be a sign that a credit shortage occurred, at least for this industry. This event could have been caused by the huge distress banks were experiencing as well as all the austerity measures implemented during those years, due to the bailout applied in Portugal by TROIKA. However, the robustness tests demonstrated that this evidence was relatively weak. We also have found some interesting results relative to the determinants of the literature included in the models.